ISTIHSAN DAN PEMBARUAN DALAM HUKUM ISLAM - Baharuddin, Ahmad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
This paper examines the two principal discussion, which is the essence of the method of istihsan and the application form in renewal of Islamic law. Istihsan is one method that disputed the jurists because of epistemology base ascribed to human reason. Nevertheless, the application form has provided renewal in Islamic law. Islamic legal thought products such as Law, Jurisprudence, compilation of Islamic law (KHI), and the Fatwa has given new jurisprudence products. Islamic marriage must go through the recording weddings and civil liability for the biological parents of the child is an example that is close to epistimologi Istihsan.